Radiotracer studies of interfaces - Horanyi, G. (Interface science and technology ;, 2004)
This volume presents a selection of examples illustrating the application of radiotracer studies for different types of interfaces. The value of radiotracer studies in fields such as food chemistry, corrosion of metals, neurochemistry, biology and catalysis is revealed. Separate chapters are devoted to the environmental problems connected with nuclear reactors and with the nuclear industry in general. The book also presents efforts to minimize and avoid the risk of radioactive contamination in the environment by describing new approaches to the problem. * Demonstrates the use of radiotracers * Contains a detailed discussion of double-layer phenomena * Separate chapters are devoted to the most important branches of science where radiotracer study of interfacial phenomena plays an important role.